Funkcionirovanie kardiorespiratornoj sistemy i jenergoobespechenie organizma kvalificirovannyh lyzhnic-gonshhic pri prohozhdenii podemov razlichnoj slozhnosti - Khmelnytska, J.; Filippov, M. (Science in Olympic Sport, 2018)
Objective. To study the main functional changes in the body of skilled female skiers as they ascend slopes of various difficulties. Materials and methods. Theoretical analysis of data from special scientific and methodological literature; study of the changes in the cardiorespiratory system; the contribution of aerobic and anaerobic energy supply to performance, depending on topography and other characteristics of the track, was analysed using the Metamax 3B gas analysis system (Cortex, Germany), the Vario Photometer II photometric biochemical analyzer (Diaglobal, Germany), and GPS sensor of the telemetric monitor Polar RS800 (Polar, Finland); pedagogical experiment, in which 10 skiers of the Ukrainian national team took part. Results. Uphill skiing on slopes of various lengths and steepness is associated with a certain functional stress on the body and changes in the cardiorespiratory system that affect the efficiency of further movement on the downhill and plain sections of the track, while the ratio of aerobic and anaerobic capacities varies as dictated by the topography of the track. The positive effect of the use of the energy supply features of athletes in the different track sections is shown. The assessment of the functional capabilities of the body during the movement on the known competitive track makes possible the focused teaching female cross country skiers to apply rational tactics of uphill skiing on slopes of various steepness and contributes to the increase in the special preparedness of the athletes. The latter was confirmed by the logical rational change by the athletes of the chosen variation in skiing velocity on the track. Conclusions. The effectiveness of uphill skiing on the slopes of various difficulties in cross-country skiing races depends on the capabilities to use anaerobic energy supply mechanisms that to a large extent affects the sports performance.